PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN PELATIHAN TERHADAP KINERJA KARYAWAN DENGAN KOMPENSASI SEBAGAI VARIABEL MODERATING PADA BNI SYARIAH CABANG PEKALONGAN - Muhammad Rifqi; Rinda Asytuti (Politeknik Negeri Medan, 2020)
This study aims to determine the effect of organizational culture, motivation, and training on employee performance with compensation as a moderating variable. The population in this study were all employees of BNI Syariah Pekalongan Branch as many as 50 people. Data collection techniques using a questionnaire. Data were analyzed using moderation regression analysis with the interaction test method. The results of this study indicate that organizational culture, motivation, and training partially have a positive and significant effect on employee performance; compensation does not moderate the effect of organizational culture on employee performance; compensation moderates the influence of motivation on employee performance; and compensation moderates the effect of training on employee performance.